Designing a mobile application interface to support mid-career professionals in creating better financial futures - Pentz, Audrey (Department of Statistical Sciences, 2021)
South Africans borrow more and save less than other nations (Discovery Bank, 2018). One reason is a lack of financial knowledge. If a mobile application could guide individuals to modify their financial habits slightly by spending less and saving more, they could dramatically improve their financial future. When designing visualisation systems such as a mobile application interface, users' qualitative design feedback and quantitative usability evaluation are both important and complementary. The benefit of usability feedback in software development is undisputed. The importance of qualitative design feedback from users however, seems to be controversial in Science. Gathering users' qualitative design feedback, ahead of usability evaluation, can have a substantial impact on downstream development costs. The researcher used design as a tool for thinking (imagining new possibilities) and communicating (sharing ideas). The purpose was to clarify ways in which a mobile application interface could support users in making better financial decisions and creating better financial futures for themselves and consequently for society. A user centred design (UCD) approach was followed, emphasising design before development, with a strong focus on user involvement in all three phases, namely requirements gathering, design and evaluation. A primary client archetype for mid-career professionals was developed, split into two personas, Alan and Zoe, based on personality and self-rated motivational attributes which were used in an unconventional way to inspire two parallel, diverse designs. In early design stages, before an idea is well formed, producing multiple contrasting designs in parallel and qualitative design feedback from users is beneficial to establishing utility (solving the right problem), tapping into users' domain knowledge, improving the quality of the design and reducing fixation on one idea. Once the concept has been socialised and evolved sufficiently with users' input, converging on one final design and testing usability (solving the problem in the right way) become more important. This research offers two refinements of the UCD process guidelines for the benefit of researchers and practitioners.